Prioritizing risk factors and identifying target areas to address with interventions to improve sustainable employment of persons with a brain injury or a spinal cord injury - A multi-stakeholder consensus process - Monika E. Finger; Katarzyna Karcz; Katarzyna Karcz; Barbara Schiffmann; Julia Eugster; Melissa Selb; Melissa Selb (Frontiers Media S.A., 2023)
BackgroundAchieving sustainable long-term employment is the goal of work integration for persons with acquired brain injury (ABI) or spinal cord injury (SCI). However, decreasing employment rates over time for persons with ABI and SCI indicate that remaining employed in the long-term is a challenge.PurposeTo identify the most important risk factors that pose a barrier to sustainable employment of persons with ABI or SCI from a multi-stakeholder perspective, and to propose corresponding interventions that address them.MethodsMulti-stakeholder consensus conference and follow-up survey.ResultsFrom 31 risk factors to sustainable employment of persons with ABI or SCI identified in previous studies, nine were defined as most important to address with interventions. These risk factors either impacted the person, the work environment or service provision. Potential interventions to address these factors were proposed in mixed condition groups, of which ten were voted on as priority interventions. The follow-up survey revealed strong agreement on the intervention proposals, strong to moderate agreement on impact, but moderate to low feasibility, as most of the interventions were measures at the meso- (service) and macro- (legislation and state regulation) level.ConclusionsHolding micro-level stakeholder conferences is a valuable method for identifying the most important risk factors to sustainable employment and for developing measures to address them. To implement measures that involve decisions at the meso- or macro-level, representatives from these levels of the healthcare and social system have to be involved.